Hemodynamic and Genetic Associations with the Risk of Idiopathic Pulmonary Arterial Hypertension Development in an Ethnic Cohort of Kazakhs - Dana Taizhanova; Togzhan Nurpissova; Gulshara Abildinova; Tamilla Martynyuk; Nazgul Kulmyrzayeva; Elena Zholdybayeva (Diagnostics)
Introduction: Idiopathic pulmonary arterial hypertension (IPAH) is a progressive and fatal disease. The aim of this study was to evaluate the association of polymorphism of the type 2 bone morphogenetic protein receptor gene (BMPR2) with the risk of IPAH development in an ethnic group of Kazakhs. We also describe the clinical and hemodynamic characteristics and outcomes of patients with and without carriers of BMPR2 gene mutations in IPAH. No available research highlights this problem in an ethnic group of Kazakhs. Materials and methods: A total of 53 patients of only Kazakh nationality with IPAH participated in the study. Clinical, functional, and hemodynamic characteristics, as well as the outcome of the disease, were compared among carriers and non-carriers of the BMPR2 mutation. Results: When receiving IPAH diagnosis, the average age of patients was 40.0 (32.0–48.0) years. Women predominated among the patients (86.8%). Of these, 17 (32.0%) were carriers of the gene mutation, and 36 (68.0%) did not have this mutation. The results of our research demonstrate that the Rs17199249 variant in BMPR2 contributed to increased susceptibility to IPAH. The T allele was associated with an increased risk of IPAH, with T = 75 (70.75%), G = 31 (29.24%), MAF—0.2925, x2—0.001, and HWE p—0.975. Carriers of the BMPR2 mutation were predominantly women (80.0%), and they had higher pulmonary vascular resistance (8.7–14.9 vs. 5.9–12.6 WU; p = 0.038), a low cardiac index (1.9–2.6 vs. 2.3–3.1 L/min per m2; p = 0.027), and a shorter time to death (p = 0.022). Conclusions: This is the first study of the genetic causes of IPAH that demonstrates the genetic polymorphism of BMPR2 is associated with an increased risk of IPAH developing with worse hemodynamic parameters and clinical outcomes.